Intestinal Microbiota Shifts towards Elevated Commensal Escherichia coli Loads Abrogate Colonization Resistance against Campylobacter jejuni in Mice - Haag, Lea-Maxie; Fischer, André; Otto, Bettina; Plickert, Rita; Kühl, Anja A.; Göbel, Ulf B.; Bereswill, Stefan; Heimesaat, Markus M. (PLOS ONE, 2012)
Background The zoonotic pathogen Campylobacter jejuni is a leading cause of bacterial foodborne enterocolitis in humans worldwide. The understanding of immunopathology underlying human campylobacteriosis is hampered by the fact that mice display strong colonization resistance against the pathogen due to their host specific gut microbiota composition. Methodology/Principal Findings Since the microbiota composition changes significantly during intestinal inflammation we dissected factors contributing to colonization resistance against C. jejuni in murine ileitis, colitis and in infant mice. In contrast to healthy animals C. jejuni could stably colonize mice suffering from intestinal inflammation. Strikingly, in mice with Toxoplasma gondii-induced acute ileitis, C. jejuni disseminated to mesenteric lymphnodes, spleen, liver, kidney, and blood. In infant mice C. jejuni infection induced enterocolitis. Mice suffering from intestinal inflammation and C. jejuni susceptible infant mice displayed characteristical microbiota shifts dominated by increased numbers of commensal Escherichia coli. To further dissect the pivotal role of those distinct microbiota shifts in abrogating colonization resistance, we investigated C. jejuni infection in healthy adult mice in which the microbiota was artificially modified by feeding live commensal E. coli. Strikingly, in animals harboring supra-physiological intestinal E. coli loads, colonization resistance was significantly diminished and C. jejuni infection induced enterocolitis mimicking key features of human campylobacteriosis. Conclusion/Significance Murine colonization resistance against C. jejuni is abrogated by changes in the microbiota composition towards elevated E. coli loads during intestinal inflammation as well as in infant mice. Intestinal inflammation and microbiota shifts thus represent potential risk factors for C. jejuni infection. Corresponding interplays between C. jejuni and microbiota might occur in human campylobacteriosis. Murine models introduced here mimick key features of human campylobacteriosis and allow for further analysis of immunological and molecular mechanisms of C. jejuni – host interactions.